1986
DOI: 10.4141/cjas86-009
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin Immunization and Growth of Lambs

Abstract: . 1986. Somatostatin immunization and growth of lambs. Can. J. Twenty cross-bred lambs were used in a replicated design to measure the growthpromoting effect of immunization against somatostatin. The lambs were immunized against human alpha-globulin (control) or against somatostatin coupled to human alpha-globulin in a l:3.75 ratio (wtiwt) (SI)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1
1

Year Published

1987
1987
1999
1999

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 6 publications
2
17
1
1
Order By: Relevance
“…In the present study, immunization alone had little effect on plasma IGF-1 concentrations but in the presence of cimaterol, plasma IGF-1 concentrations were significantly reduced compared with control animals. This was unexpected but Laarveld et al (1986) and Trout and Schanbacher (1990) observed no increase in plasma IGF-1 concentrations in SRIFimmunized steers while Magnan et al (1995) observed a significant (P < 001) reduction in SRIFimmunized sheep and only observed an increase in plasma IGF-1 concentrations in bulls after the fourth immunization (12 weeks after primary immunization). In the present study the blood samples used for IGF-1 determination were taken 14 weeks after the primary immunization and it is possible that the IGF-1 response was more retarded in this study than in that of .…”
Section: Discussioncontrasting
confidence: 48%
“…In the present study, immunization alone had little effect on plasma IGF-1 concentrations but in the presence of cimaterol, plasma IGF-1 concentrations were significantly reduced compared with control animals. This was unexpected but Laarveld et al (1986) and Trout and Schanbacher (1990) observed no increase in plasma IGF-1 concentrations in SRIFimmunized steers while Magnan et al (1995) observed a significant (P < 001) reduction in SRIFimmunized sheep and only observed an increase in plasma IGF-1 concentrations in bulls after the fourth immunization (12 weeks after primary immunization). In the present study the blood samples used for IGF-1 determination were taken 14 weeks after the primary immunization and it is possible that the IGF-1 response was more retarded in this study than in that of .…”
Section: Discussioncontrasting
confidence: 48%
“…Varner et al (1980) observed higher GH concentrations but a reduced growth rate in SRIF-IMM animals. Others have reported increases in daily gain and IGI-I levels, but no change in GH concentrations (Spencer et al, 1983a;Laarveld et al, 1986), whereas Bass et al (1987) reported increased IGF-1 with no effect on GH and a slight increase in growth rate. Nevertheless, when summarizing data taken from the literature, , using meta-analysis on weighted group averages from several studies, showed that daily gain and feed intake were increased by 11.4 and 4.2%, respectively.…”
Section: Discussionmentioning
confidence: 93%
“…In sheep, Varner et al (1980) observed higher GH concentrations in SRIF immunized (SRIF-IMM) cattle, but a reduced growth rate, whereas others have reported increases in daily gain but no change in GH concentrations (Spencer et al, 1983a;Laarveld et al, 1986;Bass et al, 1987). Sun et al (1990) reported increases in live weight gain, N retention and apparent digestibility of DM and N in SRIF-IMM lambs.…”
Section: Introductionmentioning
confidence: 90%
“…A possible practical alternative is the use of immuno-neutralization. To date, passive immunization of SRIF (administration of antibodies into the animal) has not been found to have any growth stimulating effect , but active immunization appears to be a powerful, safe, effective tool to enhance growth (for a review see Spencer, 1986 (Spencer, Hallett, and Fadlalla, 1985 ;Laarveld et al, 1986), cattle (Closset et al, 1986 ;Lawrence et aL, 1986), pigs (Spencer, 1984 ;Laarveld, personal communication) and chickens .…”
Section: Somatostatinmentioning
confidence: 99%